O etanol como instrumento de desenvolvimento na política energética brasileira - Moraes, Ana Paula Bagaiolo (2018)
The central theme of this thesis is the analysis of the context of the production, commerce and consumption of ethanol in Brazil in its economic history, as well as the positioning of the country in the promotion of public policies of this sector, thus demonstrating that the product can, by its competitive advantages, promote a cleaner energy matrix, less dependence on imported energy sources, and thus move towards energy security. Since its colonization, the Brazilian economy has been based on the commodity trade, among which is sugarcane, which, although in a cyclical way, has until today an important role in the country's economy. Since the oil crisis of the 1970s, states were forced to rethink their energy matrix, a situation that was no different in Brazil, which saw the potential of biofuels produced from this raw material: ethanol. At that moment, under strong intervention and state subsidy, Proálcool was born, which allowed the product to gain an important space, as well as the cars moved by that fuel. With the improvement in the international price of oil, this matrix became discredited: the subsidies fell and Proálcool was extinguished, beginning a new period for sugar cane and its derivatives: that of deregulation, which began in 1997. Since 2008, with the creation of flex technology cars, ethanol has returned to the agenda, but in anephemeral way, since national enthusiasm was not sustained by long-term energy policies, again frustrating private initiative that bet on ethanol and generating bankruptcy of several plants. In 2015, again, the mood was turned to the Conference of the Parties (COP) 21 of the United Nations Framework Convention on Climate Change (UNFCCC), in which a more concrete commitment was made to improve the participation of biofuels in the energy matrix in Brazil, with an 18% share of bioenergy by 2030. In order for ethanol to become one of the main national energy matrixes, it is necessary to analyze the role that the State has played over time and how it should behave today to make it possible, something that can be seen from the advent of the Law n. 13,576, dated December 26, 2017, which provides for the National Biofuels Policy (RenovaBio), which promises to bring clarity, security and predictability to the production and trade of ethanol, promoting environmental, economic and social gains for Brazil.